Exploring Barriers and Solution of Students' Reading Comprehension through Question Answer Relationship Strategy in Recount Text for Fashion Major at SMK Negeri 5 Malang - Alidin, Rinaldy; Hartiningsih, Sri (BABASAL English Education Journal, 2024)
This research aims to reveal the barriers and solutions that occur to students when using the Question Answer Relationship (QAR) strategy in improving students' reading comprehension skills through recount text. The students involved in this research were students at SMK Negeri 5 Malang class X majoring in fashion design. The method used in this research is a qualitative research method with a case study design. In this research, data was collected through observations that occurred in class and interviews with English subject teachers. The QAR strategy is one of the lessons in Active Learning and this learning strategy is also known as Student-Centered. The application of the QAR strategy can build and create students' critical thinking and high order thinking. Apart from that, students can also recognize or group questions according to the answers and improve reading comprehension. The findings in this research revealed that some students experienced barriers when the teacher implemented the QAR strategy through recount text. Some students experience barriers because they lack skills in think and search question, grouping questions and finding the main idea in a text. In this research, teachers applied QAR strategy based on the Raphael Model. This research is expected to provide benefits to English teachers as one of the strategies implemented to improve students' reading comprehension.